2016
DOI: 10.1155/2016/9121843
|View full text |Cite
|
Sign up to set email alerts
|

Nao-Xue-Shu Oral Liquid Protects and Improves Secondary Brain Insults of Hypertensive Cerebral Hemorrhage

Abstract: Aim. To determine one traditional Chinese medicine (TCM) Nao-Xue-Shu oral liquid which protects and improves secondary brain insults (SBI) in hypertensive cerebral hemorrhage (HCH). Methods. 158 patients with HCH were divided into routine clinical medicine plus Nao-Xue-Shu oral liquid (n = 78) as treatment group, and routine clinical medicine (n = 80) only served as the control group. The incidence of SBI and the classification of a favorable prognosis and a bad prognosis using the Glasgow outcome scale (GOS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Studies on patients with brain injury showed that IL-6 levels were high within a few hours after brain injury and that they gradually decreased after 1-2 days (Woiciechowsky et al, 2002). One study on patients with ICH found that IL-6 and TNF-α levels decreased on day 14 (Jiang et al, 2016). In our study, IL-6 levels decreased on day 7, suggesting that the inflammatory response mediated by IL-6 had gradually reduced on day 7 after ICH.…”
Section: Discussionsupporting
confidence: 55%
“…Studies on patients with brain injury showed that IL-6 levels were high within a few hours after brain injury and that they gradually decreased after 1-2 days (Woiciechowsky et al, 2002). One study on patients with ICH found that IL-6 and TNF-α levels decreased on day 14 (Jiang et al, 2016). In our study, IL-6 levels decreased on day 7, suggesting that the inflammatory response mediated by IL-6 had gradually reduced on day 7 after ICH.…”
Section: Discussionsupporting
confidence: 55%
“…However, clinical treatments for SBI after HICH are in the hysteretic stage, so it is urgent to explore effective methods. Recently, a study found that Nao-Xue-Shu oral liquid has a markedly lower incidence of SBI, inhibits the accumulation of hematoma, improves the absorbance of hemorrhage, eliminates the toxic stimulation of peripheral brain tissue, and inhibits the accumulation of inflammatory factors [28]. Chinese medicine has the distinctive function of modulating the body or dealing with diseases, including the treatment of brain problems [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, astragalus can also protect the blood-brain barrier permeability, perform antioxidation, and prevent cerebral ischemia (Liu et al, 2012 ; Wang et al, 2013 ; Cai et al, 2014 ). Previous studies found that Naoxueshu oral liquid could improve aphasia in mixed stroke patients (Yan et al, 2015 ) and it could also protect against the occurrence of secondary brain insults and hypertensive cerebral hemorrhage (Jiang et al, 2016 ). Whether it could be useful in the treatment of ICH is still unknown.…”
Section: Introductionmentioning
confidence: 99%